Molecular Mechanisms Underpinning the Development of Obesity - Nóbrega, Clévio; Rodriguez-López, Raquel (Springer International Publishing : Imprint: Springer, 2014)
Obesity is a multi-factorial disease, in which an excess of accumulated body fat can reach levels capable of affecting health. It results from an interplay between environmental factors, eating behavior, genes, epigenetics, and neuronal stimuli. The book provides a state-of-the-art revision about the molecular mechanisms underpinning the development of obesity, reviewing the current knowledge in areas like monogenic and polygenic obesity forms, while also providing an updated view of the emerging knowledge about epigenetics, nutrigenomics, and neuronal aspects that also contribute to obesity.